SEPARATION AND JOINING - Mitanova Shakhlo Nematullaevna (International Engineering Journal For Research & Development, 2020)
It is known that separation is a phenomenon of the communicative-syntagmatic level of the language system, the level at which sentences of a certain composition are subjected to additional processing in accordance with the author's idea.Therefore, this article gives a brief explanation about the role of separation and joining in clauses.